2016
DOI: 10.1016/j.fgb.2016.07.003
|View full text |Cite
|
Sign up to set email alerts
|

A proteomic and genetic analysis of the Neurospora crassa conidia cell wall proteins identifies two glycosyl hydrolases involved in cell wall remodeling

Abstract: A proteomic analysis of the conidial cell wall identified 35 cell wall proteins. A comparison with the proteome of the vegetative hyphae showed that 16 cell wall proteins were shared, and that these shared cell wall proteins were cell wall biosynthetic proteins or cell wall structural proteins. Deletion mutants for 34 of the genes were analyzed for phenotypes indicative of conidial cell wall defects. Mutants for two cell wall glycosyl hydrolases, the CGL-1 β-1,3-glucanase (NCU07523) and the NAG-1 exochitinase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 29 publications
4
33
0
Order By: Relevance
“…Our previous proteomic analyses have identified four of the encoded gene products (GEL-1 (NCU08909), GEL-2 (NCU07253), GEL-3 (NCU01162), and GEL-5 (NCU06781)) as being cell wall proteins (Maddi et al, 2009, Maddi and Free, 2010, Maddi et al, 2012, Ao et al, 2016). We decided to focus on these four GH-72 enzymes and determine if they were important for cell wall biosynthesis in N. crassa .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Our previous proteomic analyses have identified four of the encoded gene products (GEL-1 (NCU08909), GEL-2 (NCU07253), GEL-3 (NCU01162), and GEL-5 (NCU06781)) as being cell wall proteins (Maddi et al, 2009, Maddi and Free, 2010, Maddi et al, 2012, Ao et al, 2016). We decided to focus on these four GH-72 enzymes and determine if they were important for cell wall biosynthesis in N. crassa .…”
Section: Resultsmentioning
confidence: 99%
“…It was particularly interesting that GEL-3 was among the cross-linking enzymes needed to make cell wall during conidiation. We have previously shown that GEL-3 is found in the conidia cell wall and has a conidia-specific expression pattern (Ao et al, 2016). What the two most severely affected triple mutants have in common is the loss of both gel-1 and gel-2 , a tight colonial morphology in liquid growth conditions, and a restoration of normal morphology in the presence of the osmotic stabilizer 1.5 M sorbitol.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Additional proteomic analysis indicated compositional differences between cell walls of conidia and hyphae, suggesting differential regulation of polysaccharide biosynthesis through development 48 . Mannan and galactomannan are found as glycoconjugates on cell walls.…”
Section: Building the Cell Wallmentioning
confidence: 99%